The lowering of high vowels before [r] in Latin - Cser, András (Papers in Historical Phonology, 2020)
This paper discusses a putative sound change in the early history of Latin and synchronic alternations apparently related to it. The lowering of short high vowels before the rhotic is problematic on several counts; so much so that serious doubt has been cast on its reality. On the other hand, due to widespread alternations in the morphophonology of Classical Latin it is reasonable to assume that such a lowering operated as a synchronic rule at that stage. A minor asymmetry in the relevant alternations of verbal affixes in infectum-based vs. perfectum-based formations presents an interesting problem to which I suggest two tentative explanations.